2003
DOI: 10.2135/cropsci2003.1001
|View full text |Cite
|
Sign up to set email alerts
|

Herbage Mass, Nutritive Value, and Ergovaline Concentration of Stockpiled Tall Fescue

Abstract: Tall fescue (Festuca arundinacea Schreb.) infected with an endophyte that does not produce ergot‐like alkaloids (nontoxic endophyte) has not been evaluated for herbage mass, nutritive value, and ergovaline concentration when stockpiled during winter. Our objective was to quantify these responses for tall fescue infected with a native endophyte (K31 E+), a nontoxic endophyte (HiMag NTE), and with no endophyte (HiMag E−). Responses were measured on a fine, mixed, active, mesic Oxyaquic Fragiudalfs soil monthly f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
69
2
2

Year Published

2005
2005
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(85 citation statements)
references
References 17 publications
12
69
2
2
Order By: Relevance
“…However, late effects do not seem to be a rule as the significant reduction in litter decay rate in Omacini et al (2004) was found in an 83-d study with a mean mass loss of~23 %. Another explanation for the discrepancy between ours and earlier results might be the fact that we used overwintered litter and the alkaloids had partly degraded during the winter (see Kallenbach et al 2003). Using overwintered litter to examine litter effects on N cycling is, however, justified as most of the litter enters the soil at this stage.…”
Section: Discussioncontrasting
confidence: 64%
“…However, late effects do not seem to be a rule as the significant reduction in litter decay rate in Omacini et al (2004) was found in an 83-d study with a mean mass loss of~23 %. Another explanation for the discrepancy between ours and earlier results might be the fact that we used overwintered litter and the alkaloids had partly degraded during the winter (see Kallenbach et al 2003). Using overwintered litter to examine litter effects on N cycling is, however, justified as most of the litter enters the soil at this stage.…”
Section: Discussioncontrasting
confidence: 64%
“…Composition chimique des écotypes de F. arundinacea : A l'exeption de la teneur en MAT, la compositon chimique des écotypes de F. arundinacea étudiés est comparable à celles obtenues antérieurement par certains auteurs Wilman et Moghaddam, 1998 ;Kallenbach et al, 2003 ;Flores et al, 2007). En ce qui concerne les teneurs en MAT, les valeurs obtenues dans cette étude sont nettement inférieures à celles rapportées par ces auteurs (8,0% vs 15,3 -22,1%).…”
Section: Discussionunclassified
“…Elle s'adapte aussi bien aux régions chaudes, froides, humides que sèches (Horst et Nelson, 1979 ;King et Bush, 1985 ;Carrow et Duncan, 2003 ;Hoveland, 2009). Malgré ces mutiples qualités, les défauts majeurs de la fétuque élevée sont sa médiocre appétibilité et sa faible digestibilité (Emile et al, 1992 ;Kallenbach et al, 2003 ;Flores et al, 2008 Afin de caractériser le milieu ruminal du mouton d'expérimentation au cours de l'évaluation de la dégradabilité in sacco, le pH et la concentration en azote ammoniacal (N-NH3) dans le jus du rumen ont été mésurés comme suit : Juste avant le repas du matin (0 h), 1, 3 et 7 h après. L'azote ammoniacal a été dosé par la méthode de microdiffusion de Conway (Conway, 1957).…”
Section: Introductionunclassified
“…Bagley et al, (1983) found that CP, NSC, and digestibility of the forages decreased over winter grazing from 10.6 to 9.5%, 15.9 to 5.5%, and 63.3 to 42.7%, respectively. Forage nutritive value is typically highest in the fall and deteriorates over winter (Singer et al, 2003;Kallenbach et al, 2003) as indicated by increasing ADF concentrations. Kallenbach et al (2003) found that with the mild winter conditions in Missouri, forage quality did not deteriorate quickly after mid-December.…”
Section: Stockpiled Foragementioning
confidence: 99%
“…Forage nutritive value is typically highest in the fall and deteriorates over winter (Singer et al, 2003;Kallenbach et al, 2003) as indicated by increasing ADF concentrations. Kallenbach et al (2003) found that with the mild winter conditions in Missouri, forage quality did not deteriorate quickly after mid-December. Average CP, ADF, and NDF concentrations at that time were 13, 30, and 58% in stockpiled tall fescue respectively, which should be sufficient to meet the needs of lactating and non-lactating cows.…”
Section: Stockpiled Foragementioning
confidence: 99%